Antioxidative Effects of Natural Products on Diabetic Cardiomyopathy. (18th October 2017) - Yan, Bingdi; Ren, Jin; Zhang, Qinghua; Gao, Rong; Zhao, Fenglian; Wu, Junduo; Yang, Junling
Abstract : Diabetic cardiomyopathy (DCM) is a common and severe complication of diabetes and results in high mortality. It is therefore imperative to develop novel therapeutics for the prevention or inhibition of the progression of DCM. Oxidative stress is a key mechanism by which diabetes induces DCM. Hence, targeting of oxidative stress-related processes in DCM could be a promising therapeutic strategy. To date, a number of studies have shown beneficial effects of several natural products on the attenuation of DCM via an antioxidative mechanism of action. The aim of the present review is to provide a comprehensive and concise overview of the previously reported antioxidant natural products in the inhibition of DCM progression. Clinical trials of the antioxidative natural products in the management of DCM are included. In addition, discussion and perspectives are further provided in the present review.